2010
DOI: 10.1111/j.1743-6109.2010.01751.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Penile Size and Erectile Function after High-intensity Focused Ultrasound and Targeted Cryoablation for Localized Prostate Cancer: A Prospective Pilot Study

Abstract: Introduction Erectile dysfunction (ED) represents a common quality-of-life issue of any treatment used for prostate cancer, including high-intensity focused ultrasound (HIFU) and targeted cryoablation of the prostate (TCAP). There is a paucity of comparative studies regarding the difference in the erectile function and penile size of patients undergoing HIFU or TCAP. Aim The aim of this study is to compare the erectile functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
(54 reference statements)
0
18
0
Order By: Relevance
“…We did not see the trend in this study, probably due to significantly older age in the patients of HDRBT. Another prospective study revealed that patients of HIFU had continuously better postoperative IIEF scores than cryoablation for 3 years (Li et al 2010). Our results were compatible with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…We did not see the trend in this study, probably due to significantly older age in the patients of HDRBT. Another prospective study revealed that patients of HIFU had continuously better postoperative IIEF scores than cryoablation for 3 years (Li et al 2010). Our results were compatible with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…14,17 The main finding of our study is that the ondemand use of erectile aids was identified as the only independent predictive factor to restore postoperative IIEF-5 scores by multivariate analysis. The effect of PDE5 inhibitors have been unclear in the prostate cryoablation setting to date, since most series reported full treatment such as routine penile rehabilitation, 2,12,16 as well as lacking information about use of erectile aids, 2,13 which resulted in no information to compare between erectile aid users and non-users. In our study, erectile aids can clearly restore postoperative IIEF-5 scores to that of the preoperative score by the end of the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…11 In terms of EF after cryoablation, there are only a few articles reporting longitudinal changes using either direct interview 12,13 or validated instruments. [14][15][16] Those reports describe that 39.0-51.3% of patients recover EF with penile rehabilitation or using erectile aids. Although prostate cryoablation has been reported to impair EF, likely resulting from freezing bilateral cavernous nerves close to the apex, one explanation for those men recovering EF may be due to nerve regeneration after freeze damage mentioned by several investigators in animal and human studies.…”
Section: Discussionmentioning
confidence: 99%
“…Focal ablative therapies are mostly performed under transrectal ultrasound guidance (Table 1) This non-invasive method of monitoring temperature shows excellent results in canine prostates [39] and is performed in focal laser therapy and transurethral HIFU [40].…”
Section: Image Guidance During Treatmentmentioning
confidence: 99%